Novel Organometallic Chalcones Functionalized with a Crown Ether Fragment as Optical Ion Chemosensors - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Agurto-Doren, N; Agurto-Doren, N; Maldonado-Hernandez, T; Maldonado-Hernandez, T; González-Sepúlveda, R; González-Sepúlveda, R; Flores-Vergara, E; Flores-Vergara, E (John Wiley and Sons Ltd, 2018)
We previously reported the synthesis and characterization of new organometallic chalcones derived from ferrocene, cyrhetrene and cymantrene functionalized with a benzo-15-crown-5 fragment. The ferrocene and cyrhetrene chalcones have been investigated as chemosensors for metal ions with optical response in acetonitrile. Several metal ions were selected considering the diameter of the cavity and the charge-to-radius ratio of the cation. The stoichiometry of the complexes was determined using Job s method. It was found that Na+ and Ca2+ complexes have a 1:1 stoichiometry while a 2:1 (metaloligand-to-cation) stoichiometry was determined for Ba2+ and Pb2+ complexes. The association constants were calculated according to the stoichiometry of the complex and the results showed that they are directly affected by the electron-withdrawing nature of the organometallic fragment. Moreover, complexes of ferrocenyl chalcone have larger association constants than those of the cyrhetrenyl analogue. This experimental observation is consistent with the electronic properties of the ferrocenyl fragment. Copyright © 2017 John Wiley & Sons, Ltd.